2011
DOI: 10.1007/s00520-011-1263-0
|View full text |Cite
|
Sign up to set email alerts
|

The comparative effectiveness of a team-based versus group-based physical activity intervention for cancer survivors

Abstract: These hypothesis-generating findings suggest that a short-term, team-based physical activity program (dragon boat paddling) was associated with increased cohesion and adherence/attendance. Improvements in physical fitness and psychosocial benefits were comparable to a traditional, group-based walking program. Compared to a group-based intervention delivery format, the team-based intervention delivery format holds promise for promoting physical activity program adherence/attendance in cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…Numerous other studies have identified group-based physical activity as a way of building up self-confidence, contributing to feelings of being normal, and as a social mediator of disease in cancer patients (Midtgaard et al, 2006), without exploring the potential of team-based sport. For instance, our findings are comparable with a recent study of Carter et al (2012), which demonstrated how participation in outdoor team-based sport (i.e., dragon boat racing) in comparison with a group-based walking program increases attendance and adherence to physical activity among cancer patients (Carter et al, 2012). Our study goes beyond this and suggests that playing football facilitated a mental and physical closeness between the men, which permitted intimacy, mutual caring, and sharing of concerns and experiences related to disease and treatment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Numerous other studies have identified group-based physical activity as a way of building up self-confidence, contributing to feelings of being normal, and as a social mediator of disease in cancer patients (Midtgaard et al, 2006), without exploring the potential of team-based sport. For instance, our findings are comparable with a recent study of Carter et al (2012), which demonstrated how participation in outdoor team-based sport (i.e., dragon boat racing) in comparison with a group-based walking program increases attendance and adherence to physical activity among cancer patients (Carter et al, 2012). Our study goes beyond this and suggests that playing football facilitated a mental and physical closeness between the men, which permitted intimacy, mutual caring, and sharing of concerns and experiences related to disease and treatment.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, our findings are comparable with a recent study of Carter et al. (), which demonstrated how participation in outdoor team‐based sport (i.e., dragon boat racing) in comparison with a group‐based walking program increases attendance and adherence to physical activity among cancer patients (Carter et al., ). Our study goes beyond this and suggests that playing football facilitated a mental and physical closeness between the men, which permitted intimacy, mutual caring, and sharing of concerns and experiences related to disease and treatment.…”
Section: Discussionsupporting
confidence: 90%
“…Number of children and being a member of a community organization were not associated with PA. Attendance was greater for those who were members of a team sport versus a PA group in one nonrandomized trial . Social network measures of network size, integration, and diversity and number of friendship and community ties were all positively associated, while marital, religious, and relative ties were not .…”
Section: Resultsmentioning
confidence: 93%
“…Interventions ranged from three weeks to 24 months. Only three trials had intervention outcome data that addressed the aims of this review: two studies examining the effects of interventions with versus without a partner, and a study examining a team versus group context …”
Section: Resultsmentioning
confidence: 99%
“…directed in their decision to participate. Although dragon boating requires no previous experience and allows for diverse skill sets (Carter et al, 2012), therapists should have participants obtain physician clearance prior to participation.…”
mentioning
confidence: 99%